Living with type 1 diabetes in Neno, Malawi: a qualitative study of self-management and experiences in care - Laura Drown; Alma J Adler; Leah N. Schwartz; Junious Sichali; Francis Valeta; Chantelle Boudreaux; Celina Trujillo; Todd Ruderman; Gene Bukhman (BMC, 2023)
Abstract Background The prevalence of type 1 diabetes (T1D) is increasing in low-income countries including Malawi. In this setting, care is frequently impacted by challenges in diagnosis and management. Access to high-quality T1D care remains limited in Malawi, with fairly low availability and high cost of insulin and other supplies and diagnostics, lack of T1D knowledge, and absence of readily accessible guidelines. In the Neno district, Partners In Health established advanced care clinics at district hospitals to provide comprehensive, free care for T1D and other noncommunicable diseases. Prior to this study, experiences in care for people living with T1D (PLWT1D) at these clinics remained unexplored. Here we examine the impact of living with T1D, knowledge and self-management of, and facilitators and barriers to T1D care in Neno District, Malawi. Methods We conducted a qualitative study utilizing behavior change theory that consisted of twenty-three semi-structured interviews conducted in Neno, Malawi in January 2021 with PLWT1D, their families, providers, and civil society members to explore the psychosocial and economic impact of living with T1D, T1D knowledge and self-management, and facilitators and barriers to accessing care. Interviews were analyzed thematically using a deductive approach. Results We found that PLWT1D had good knowledge and practice of self-management activities for T1D. Key facilitators to care identified by informants included extensive patient education and availability and provision of free insulin and supplies. Significant barriers included distance from health facilities, food insecurity, and low literacy/numeracy. Informants described T1D as having a notable psychosocial and economic impact on PWLT1D and their families, notably worrying about having a lifelong condition, high transportation costs, and reduced working ability. While home visits and transport refunds helped facilitate access to the clinic, informants reported the refunds as inadequate given high transport costs faced by patients. Conclusions T1D was found to have a significant impact on PLWT1D and their families. Our findings represent important areas of consideration in design and implementation of effective programs for treating PLWT1D in resource-limited settings. Facilitators to care identified by informants may be applicable and beneficial in similar settings, while persisting barriers represent areas for continued improvement in Neno.